Emergency Pneumonectomy: A Life-Saving Measure for Severe Recurrent Hemoptysis in Tuberculosis Cavitary Lesion - Ravisagar Patel; Abhinav Singh; Rajendra Mohan Mathur; Anula Sisodiya (Case Reports in Pulmonology)
Hemoptysis constitutes a common and urgent medical problem. Swift and effective management is of crucial importance, especially in severe, life-threatening cases. Because of bronchial artery or a branch of pulmonary artery erosion due to cavitary infiltration, bronchiectasis, fungus ball, broncholithiasis, or destroyed lung, the bleeding can lead to highly compromised gas exchange or sometimes can be a life-threatening situation. Chest computerized tomography and bronchoscopy remain the methods of choice for lateralization of the disease. Some patients can be treated successfully with endobronchial interventions. Bronchial artery embolization can be rewarding in some patients but the recurrence rate is higher in tuberculosis than other etiologies of hemoptysis. Surgical resection of the lung, mainly lobectomy, remains a life-saving procedure but it should be performed very selectively to avoid higher postoperative morbidity and mortality.